Vitamin D supplementation to palliative cancer patients: protocol of a double-blind, randomised controlled trial 'Palliative-D'. Issue 4 (13th September 2017) - Helde-Frankling, Maria; Bergqvist, Jenny; Klasson, Caritha; Nordström, Marie; Höijer, Jonas; Bergman, Peter; Björkhem-Bergman, Linda
Abstract : Background: According to a small pilot study on palliative cancer patients at our ward, vitamin D supplementation had beneficial effects on pain (measured as opioid consumption), infections and quality of life (QoL) without having any significant side effects. Objective: The primary objective of the 'Palliative-D' study is to test the hypothesis that vitamin D supplementation for 12 weeks reduces opioid consumption. The secondary objectives are to study if reduction of antibiotic consumption and fatigue as well as improvement in QoL assessments can be observed. Effect on the 25-hydroxy vitamin D (25-OHD) levels in serum after 12 weeks of treatment will be studied, as well as the change in opioid dose in relation to genetic polymorphism in genes involved in the effect and metabolism of vitamin D. Method: A randomised, double-blind placebo-controlled multicentre trial has been designed. The trial will include 254 adult palliative cancer patients with 25-OHD levels <50 nmol/L and a life expectancy of more than 3 months recruited from two advanced palliative home care centres in Stockholm. Included patients will be randomly assigned to 12 weeks of treatment with cholecalciferol (vitamin D3) 4000 IU/day or placebo. The study will start in November 2017 and will finish in December 2019. The study is approved by the Regional Ethical Committee, Dnr2017/405-31/1, by the Swedish Medical Products Agency, EudraCT: 2017-000268-14, and is registered at Clinicaltrial.gov: NCT03038516 . The study is financed with research grants from the Swedish Cancer Society and the Stockholm County Council.